2018
DOI: 10.1017/s0954579418001244
|View full text |Cite
|
Sign up to set email alerts
|

Reports of perceived racial discrimination among African American children predict negative affect and smoking behavior in adulthood: A sensitive period hypothesis

Abstract: We examined the prospective relations between a cultural risk factor, perceived racial discrimination (PRD), and subsequent negative affect and health behavior (smoking) in a panel of 889 African American children (part of the Family and Community Health Study). Cultural moderators (protective factors) of these relations were also examined. PRD was assessed six times from ages 10.5 (Wave 1) to 24.5 (Wave 6), and negative affect (anger and depressive symptoms) was assessed at Wave 2 (age 12.5) and Wave 6 (age 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…In a novel finding, we saw that Aboriginal children exposed to racism had seven times the risk of trying cigarettes at ages 10–12 compared to unexposed children. The strong, albeit imprecise, effect of racial discrimination on trying cigarettes found in our study is reflected in longitudinal studies conducted in both the United States and United Kingdom examining childhood exposure to racism as a predictor of later smoking behaviour, though both studies measured smoking behaviour in adulthood (21–25 years) [50, 51]. Studies in child (6–11 years) and adolescent (12–18 years) populations are broadly mixed, with around half of studies finding a significant positive association between racism and smoking [12].…”
Section: Discussionmentioning
confidence: 94%
“…In a novel finding, we saw that Aboriginal children exposed to racism had seven times the risk of trying cigarettes at ages 10–12 compared to unexposed children. The strong, albeit imprecise, effect of racial discrimination on trying cigarettes found in our study is reflected in longitudinal studies conducted in both the United States and United Kingdom examining childhood exposure to racism as a predictor of later smoking behaviour, though both studies measured smoking behaviour in adulthood (21–25 years) [50, 51]. Studies in child (6–11 years) and adolescent (12–18 years) populations are broadly mixed, with around half of studies finding a significant positive association between racism and smoking [12].…”
Section: Discussionmentioning
confidence: 94%
“…Several papers included in the Special Issue focused on racism, racial discrimination, racial segregation, and unfair treatment as cultural risk factors in development. Gibbons, Fleischli, Gerrard, and Simons (2018) investigated the prospective relations between racial discrimination and subsequent negative affect (anger and depressive symptoms) and smoking in a sample of 889 African American children. Racial discrimination at Wave 1 predicted smoking at Wave 6, controlling for multiple factors.…”
Section: Equifinality and Multifinality In Cultural Developmentmentioning
confidence: 99%
“…These associations have been found in relation to both racial microaggressions (Torres-Harding, Torres, & Yeo, 2020) as well as overt racial discrimination (Paradies et al, 2015) and across the life span, including in children (Priest et al, 2013), adolescents (Benner et al, 2018), and adults (Pieterse, Todd, Neville, & Carter, 2012). Although the majority of work has used cross-sectional designs, a number of studies have reported empirical support for longitudinal associations between racial discrimination and mental health outcomes (e.g., Gibbons, Fleischli, Gerrard, & Simons, 2018; Kwate & Goodman, 2015; Walker et al, 2017). Nevertheless, the validity and utility of this large body of work has come into question in recent years (Lilienfeld, 2017), in part because of racial discrimination researchers’ alleged neglect of important third variables that may account for the relationship between experiences of racial discrimination and negative outcomes.…”
mentioning
confidence: 99%
“…Furthermore, longitudinal studies do not support the assertion that ongoing internalizing psychopathology serves as a risk factor for perceiving more racial discrimination. For example, several studies (e.g., Gibbons et al, 2018; Watson-Singleton, Mekawi, Wilkins, & Jatta, 2021) have found that although perceived racial discrimination predicts future depression among African Americans, depression does not predict future perceptions of racial discrimination. Even stronger evidence can be found in Ong and Burrow’s (2018) daily diary study, which found that reactivity in response to racial discrimination was associated with later depressive symptoms even when accounting for individuals’ expectations of being racially discriminated against (e.g., stigma consciousness) among African American graduate and postgraduate students.…”
mentioning
confidence: 99%